HIGH DOSES OF BISPHENOL-A PROMOTE A REDUCTION IN THE NUMBER OF MYENTERIC NEURONS IN RATS - Favetta, Paula Montanhini; Otutumi, Luciana Kazue; Soares, Andreia Assunção; Colla, Itaruã Machri; Trindade, Wesley Alves; Geronimo, Edson; Furlan, Anna Clara de Melo; de Souza, Giovana Vitória Vieira; Vigo, Maria Eduarda Lopes da Silva; Caetano, Ana Laura Bosco; Germano, Ricardo de Melo (ARACÊ, 2024)
Bisphenol-A (BPA), found in plastics and food coatings, is known for its potential adverse health effects. While some studies have focused on BPA's endocrine effects, other research explores its impact on the myenteric plexus, which controls the motility of the digestive tract. The study investigated the effects of BPA on myenteric plexus neurons in rats. For the analysis of the effects on the myenteric plexus (MP), 32 male Wistar rats aged 40 days were divided into four groups (n=8) that received filtered water via gavage over 12 weeks for the control group (CG), dose group 1 (DG1) BPA solution at 0.05mg/kg, dose group 2 (DG2) BPA solution at 0.25mg/kg, and dose group 3 (DG3) BPA solution at 0.5mg/kg. The animals were weighed weekly to adjust the administered volume. At the end of the experimental period, a new weighing was performed, and the rats were euthanized. After laparotomy, the intestinal segments corresponding to the jejunum-ileum were collected to demonstrate the density of the population (Giemsa+), the subpopulations of active myenteric neurons (NADH-d+), and the nitrergic subpopulation (NADPH-d+). BPA exposure did not significantly affect the rats' weight gain, but, there was a reduction in the total density of myenteric neurons in DG3 (10.78mm²) compared to DG (18.88mm²) and DG1 (16.28mm²), and also a reduction in the NADH-d+ subpopulation between DG3 (8.50mm²) and the CG (14.45mm²) and DG1 (14.17mm²) groups. For the nitrergic subpopulation (NADPH-d+), there was no difference in the expression of these neurons. Based on the results obtained, it can be inferred that there was a reduction in cholinergic neurons (NADPH-d-), calculated from the total population of neurons. These findings suggest that BPA may compromise the neuronal function of the MP, possibly by inducing oxidative stress and apoptosis of subpopulations, acting as a xenoestrogen on the nuclear receptors of these neurons, and consequently affecting the regulation of gastrointestinal motility, interfering with cholinergic neuronal transmission and nitric oxide production, and also greater resistance of nitrergic neurons can be observed. Both studies highlight the importance of raising awareness about BPA, as well as the possible harmful effects on unique health. The need to understand the impacts of BPA on different biological systems is emphasized to better understand its effects on human health, especially considering its widespread presence in modern society.